(NON) HUMAN(IMAL) RIGHTS: DISMANTLING THE SEPARATENESS IN LAW AND POLICY - WILSON, AMY P. (Society Register, 2019)
In 2016, the South African Constitutional Court recognised that the guaranteed human right to the environment, as contained in the Constitution, includes animal welfare. In its judgment, the court stated that the suffering of individual animals is correctly linked to conservation and that this “illustrates the extent to which showing respect and concern for individual animals reinforces broader environmental protections. Animal welfare and animal conservation together reflect two intertwined values”. Although the effect of the statement by the highest court in the land is yet to be fully realised, the court unambiguously demonstrated in its ruling the clear link between human rights and animal interests. These interests are not only to be interpreted in the broad sense relating to species-conservation, but rather the interests and welfare of individual animals. Building on from this approach and the rationale provided by the court, this Paper looks to explore more broadly the interaction and linkages between human and animal rights and interests. More particularly, it attempts to illustrate how these concepts may reinforce and enrich one another and how this relationship may be better reflected in law and policy. It will argue that sophisticated democracies and movements require an integrational approach. By expanding the scope and interpretation of certain human rights to include animal interests; and through coordinated, targeted efforts – we ensure notion of justice is achieved, for all who require it.